Tricuspid insufficiency after cardiac-implantable electronic device placement - Nismat Javed (Taylor & Francis Group, 2021)
Objective Device-related estimates of incidence and significance of tricuspid regurgitation (TR) is mainly based on case reports and small observational studies. We sought to determine whether right-heart device implantation increased the risk of TR in this interventional study. Methods All patients who underwent permanent pacemaker (PPM) or other device implantation were assessed for degree of TR at one year. The data collected was analyzed on IBM SPSS version 26. Descriptive statistics were applied for qualitative variables. Mean and standard deviation were applied for quantitative variables. Regression analysis and paired t-tests were applied for the degree of change and predictors of TR. Results Out of 165 participants, 73.94% were male. The mean age of the participants was 59.86 ± 12.03 years. Dual-chamber pacemaker (DDDR) was the most common device implanted (78.18%) causing significant TR and drop in left ventricular ejection fraction as compared to other devices (p-value < 0.05). The paired t-test for changes in ejection fraction (LVEF) and TR were also significant (p-value < 0.05). A regression model predicted significant TR to depend on baseline LVEF (p-value < 0.05). Conclusion Device-related worsening of TR is related to mechanical mechanisms. It is significantly associated with DDDR pacemakers after a 1-year follow-up.